Reviews and comparisons physiological and performance responses of wrestlers to rapid and gradual weight loss methods - Delphan, M.; Rashidlamir, A. (International Journal of Wrestling Science, 2013)
Weight maintenance is much more essential for better performance and more desirable results in sport matches such as wrestling, weightlifting and judo. Failures in weight management have led to vast research on the mechanisms which are involved in this phenomenon. Weight control and the type of weight loss methods used to reach the ideal weight, are important factors in wrestling, and these methods have also a great impact on the competitive performance of wrestlers and their sport lifespan. According to several reports about rapid weight loss, it has been found that despite the repeated warnings from medical and sports organizations and the well documented destructive effects of rapid weight loss methods on physiological organs of the body, there is a high prevalence of use among wrestlers, including high school, collegiate and international style wrestlers. These rapid methods result in weight loss by 3 to 6 percent, in the interval time of 24 to 72 hours before the competition, in order to reach their weight class limit. It has also reported that 3% to 20% of weight loss can happen in pre-seasons of last days or the day before weigh in. There have been deaths due to the utilization of these methods. Hence, the aim of this study was to review of evidence which has been carried out in the field of weight loss methods, including rapid weight loss, traditional and gradual methods and document the effects on the performance and physiological variables in wrestlers. Hence, we compared these methods and provided the best method based on current scientific evidence. METHODS: Numerous studies have been conducted on the problem of weight loss in athletes. These studies have been conducted in different methods, including: poor diet (severe and gradual food restriction), changes in eating habits of athletes, dehydration from intense exercise, limiting drinking water, impermeable clothing, warm environment (saunas, steam room), diuretic pills and vomiting. Hence, several studies have demonstrated that functional and physiological variables of wrestlers were destroyed by rapid weight loss methods. Among these methods, the only method of weight loss which has been promising to solve this dilemma is gradual weight loss (twelve-day). It has been shown that this method had no adverse effects on the body's performance and physiological variables of elite wrestlers compared to those who used rapid weight loss methods, respectively. Then, subsequent studies used this method (twelve-day) plus aerobic exercise on overweight and obese individuals and confirmed their findings. Furthermore, recently, it has shown that twelve-day weight loss method which was performed by elite wrestlers, it also had no significant effect on AgRP levels (a powerful orexigenic peptide which is secreted by the arcuate nucleus of the hypothalamus, and plays an important role in weight control). This method also decreased body fat percentage and body weight, whereas rapid weight loss led to decreased body weight, increased AgRP levels and unchanged body fat percentage. Accordingly, it should be acknowledged that the twelve-day method is more effective and the best method observed at the present time. FINDINGS: We found that traditional methods alone or together have deleterious effects on cardiovascular function, electrical activity, thermal regulation, renal function, electrolyte balance, body composition, muscular strength and endurance, aerobic performance, vigor, short-term memory and cognitive-perceptual. These methods also increase energy disorders and increases brain neuropeptide of AgRP which involved in appetite, energy balance and weight management. The method of gradual weight loss (twelve-day) did not cause a reduction of muscular strength and endurance, but also it improves body fat percentage and leads to stability of resting plasma IL-6 and brain neuropeptide of AgRP levels. CONCLUSION: Many studies of weight loss have shown the negative effects of rapid weight loss and traditional protocols on physiological function and athletic performance of wrestlers. Hence, utilize these methods will lead to decline of sport`s lifetime and health of wrestlers and will encounter them with serious risks. Among these, the twelve-day weight loss program which is done before the competition, may be a suitable method to replace the traditional methods. Hence, this article attempted to review the scientific evidence of weight loss methods in wrestling, highlighting the risks which are caused by rapid weight loss, and also suggested the best weight loss methods considering scientific evidence to coaches and athletes.